Study on the indoor environmental performance of complex insulation material: Carbonized rice hull and glass wool - Yin, Cheng Ri; Yeom, Dongwoo; Lee, Kyu In (Indoor and Built Environment, 2018)
The purpose of this study is to make a complex insulation material with carbonized rice hull and glass wool and to verify the environmental control performance. Full-scale experimental mock-ups were constructed, and the control performance in an indoor environment was compared and verified through monitoring experiments. The complex insulation mock-up showed a relatively high temperature during spring, summer and autumn. The difference in the heat storage capacity of the materials was the cause for this difference. Also, the complex insulation material was proven as more effective at maintaining the stability of the indoor environment and temperature during spring, summer and autumn. In addition, the complex insulation was able to control the indoor humidity at a comfortable level during every season. Our results have therefore verified that the carbonized rice hull was effective at controlling the indoor humidity. When compared with the pure carbonized rice hull insulation, the complex insulation wall was relatively thin; therefore, more net indoor area could be achieved by using the complex insulation material. In addition, if self-produced, the complex insulation could be economically more feasible. Therefore, this complex material was synthetically proven to have merits for insulation of lightweight timber houses for thermal comfort of occupants.
Keywords: Carbonized rice hull; Indoor environment; Natural insulation material; Thermal comfort